Peran Motivasi dalam Memoderasi Pengaruh Pengetahuan Artificial Intelligence, Self-Efficacy, dan Parental Influence terhadap Minat Berkarir sebagai Akuntan Publik - I Nyoman Hendra Aryadi; I Gede Nata Mintara; Ikbar Luqyana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The purpose of this study was to examine the factors that can influence accounting students' interest in choosing a career as a public accountant with research variables of Artificial Intelligence knowledge, self-efficacy and parental influence with motivation as a moderating variable. The population in this study were all students studying Accounting. Sampling in this study used a simple random sampling method. The number of samples used was calculated using the Slovin formula with the number of samples used being 135 students. The data analysis technique in this study was using PLS (Partial Least Square). The results of the analysis of this study prove that the variables of artificial intelligence knowledge, self-efficacy and parental influence have a positive and significant effect on students' interest in choosing a career as a public accountant, then motivation is able to moderate or strengthen the influence of artificial intelligence knowledge, self-efficacy and parental influence on Accounting Study Program Students' Interest in Choosing a Career as a Public Accountant.